A HABA dye-based colorimetric assay to detect unoccupied biotin binding sites in an avidin-containing fusion protein - Sonia Mukherjee; Pierre Leblanc; Mark C Poznansky; Ann E Sluder (BioTechniques)
Avidin-biotin binding, the most robust non-covalent protein-ligand interaction occurring in nature, has wide-ranging applications in biotechnology. A frequent challenge in these applications is accurately determining the number of unoccupied biotin binding sites in avidin-containing fusion proteins. We delineate a novel assay protocol in miniaturized format to quantify available biotin binding sites based on the affinity of the anionic dye 4′-hydroxyazobenzene-2-carboxylic acid for biotin binding sites within avidin. We apply this assay as a quality control assay to evaluate the number of available biotin binding sites in different fusion protein production batches. This method offers a streamlined alternative to fluorescence-based assays commonly employed to assess biotin binding, is less time-consuming than other methods and is applicable to diverse fusion proteins.